2018
DOI: 10.1371/journal.pone.0193438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of age-related changes in psychosine metabolism in the human brain

Abstract: α-Synuclein aggregation has been linked to Gaucher’s disease (GD) and Krabbe’s disease (KD), lysosomal conditions affecting glycosphingolipid metabolism. α-Synuclein pathology has been directly attributed to the dysregulation of glycosphingolipids in both conditions, specifically to increased galactosylsphingosine (psychosine) content in the context of KD. Furthermore, the gene (GALC) coding for the psychosine degrading enzyme galactosylceramidase (GALC), has recently been identified as a risk loci for Parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 42 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…Further supporting a role of GALC in the onset of PD, a recent study revealed reduced GALC activity and associated sphingolipid accumulation in sporadic PD patients, when compared to healthy controls . Interestingly, GALC activity was also reduced in aging, which is the strongest risk factor for PD.…”
Section: Galactosylceramidase (Galc)mentioning
confidence: 99%
“…Further supporting a role of GALC in the onset of PD, a recent study revealed reduced GALC activity and associated sphingolipid accumulation in sporadic PD patients, when compared to healthy controls . Interestingly, GALC activity was also reduced in aging, which is the strongest risk factor for PD.…”
Section: Galactosylceramidase (Galc)mentioning
confidence: 99%
“…In several animal models, as well as in patients affected by lysosomal storage disorders, such as GD, GM2 gangliosidosis, Niemann-Pick type C, β-galactosialidosis, NCL10, and Krabbe's disease, α-syn accumulation has been observed. [70][71][72] Moreover, in GD patients, levels of plasma oligomeric α-syn were found higher with respect to controls 73 and negatively associated with leucocyte GCase activity. 74 Increased plasma oligomeric α-syn levels were also found in a small group of patients affected by rarer lysosomal storage disorders, namely Niemann-Pick type C1 and C2 disease, Krabbe's disease, and Wolman's disease.…”
Section: Dysfunction Of the Alp Pathway Leads To Aggregation And Propmentioning
confidence: 88%
“…GALC catalyzes the hydrolysis of different substrates (i.e., galactosylceramide and galactosylsphingosine). Galactosylsphingosine levels were higher in the cerebral cortex of PD patients compared to age‐matched controls . Furthermore, in vitro experiments have shown that galactosylsphingosine accelerates aggregation of α‐syn in a dose‐dependent manner …”
Section: The Issue Of Alp Alterations In Sporadic Pdmentioning
confidence: 97%
See 2 more Smart Citations